Honoring the Civil War Dead : Commemoration and the Problem of Reconciliation - Neff, John R. (Book collections on Project MUSE., 2005)
By the end of the Civil War, fatalities from that conflict had far exceeded previous American experience, devastating families and communities alike. As John Neff shows, commemorating the 620,000 lives lost proved to be a persistent obstacle to the hard work of reuniting the nation, as every memorial observation compelled painful recollections of the war. Neff contends that the significance of the Civil War dead has been largely overlooked and that the literature on the war has so far failed to note how commemorations of the dead provide a means for both expressing lingering animosities and dis.